Paciente neonato a término con enfermedad de membrana hialina. - León Mayorga, Siulee Stefany (2021)
This work offers current information on what is this condition that neonates go through, how to approach this patient, both the pediatric physician and the health personnel. The methodology to be used to help the neonate to improve his situation. To be clear that hyaline membrane disease is caused by a deficit in the production of surfactant, which does not allow the recruitment of the alveolar unit and normal gas exchange. The main risk factor is prematurity; however, perinatal asphyxia, maternal diabetes, absence of antenatal corticosteroids, among others, also influence its presentation.